STUDY OF EFFECTS ON SOCIETY AND HEALTH BY USING UNNATURAL COLORS IN FOOD ITEMS: भोज्य पदार्थो में अप्राकृतिक रंगो के उपयोग से समाज एवं स्वास्थ्य पर पडने वाले प्रभावो का अध्ययन - Raj, Sadhana (International Journal of Research -GRANTHAALAYAH, 2014)
Definition of color Color has been pervading our life for thousands of years. Initially humans used natural colors. It is noteworthy that among the items found in the Indus Valley Civilization in the excavation of Mohenjodaro and Harappa, there were also statues and utensils that were dyed. In which a piece of red colored cloth was also found. According to experts, it was painted with a color prepared from the root of the majith or majishta. For thousands of years, the root of the Majit and the bark of the Bakkam tree was the main source of red color. Colors were made from peepal, sycamore and pakad, turmeric etc., but nowadays artificial colors are in use, which is not only being used heavily in clothing but also in food items. रंग की परिभाषा रंग हज़ारो वर्षो से हमारे जीवन में व्याप्त है। प्रारंभ में मानव प्राकृतिक रंगों का हि उपयोग करता था। उल्लेखनीय है कि मोहनजोदड़ो और हड़प्पा की खुदाई में सिंधु घाटी सभ्यता की जो वस्तुए प्राप्त हुई है उनमें ऐसी मूर्तियाँ एवं बर्तन भी थे जिन पर रंगाई की गई थी। जिसमें लाल रंग के कपड़े का एक टुकडा भी मिला। विषेषज्ञों के अनुसार इस पर मजीठ या मजिष्ठा की जड़ से तैयार किया गया रंग चढ़ाया गया था। हाजरों वर्षों तक मजीट की जड़ और बक्कम वृक्ष की छाल लाल रंगा का मुख्य स्त्रोत थी। पीपल, गूलर और पाकड़, हल्दी आदि से रंग तैयार किया जाता था किंतु आजकल कृत्रिम रंगो को उपयोग जोरो पर है जो न सिर्फ कपडो बल्की भोज्य सामग्रीयों में अत्यधिक उपयोग किया जा रहा है।